LOCATING ASPERITIES BY MEANS OF STOCHASTIC ANALYSIS OF SEISMIC CATALOGS - Arvanitakis, K.; Gounaropoulos, C.; Avlonitis, M. (Bulletin of the Geological Society of Greece, 2016)
In this study it is proposed that spatially detecting low b values in certain segment faults in conjunction to the spatial earthquake density of the corresponding areas, can be used in order to locate faults asperities. This hypothesis is tested in the area of Corinth Gulf where we have processed data from the earthquake catalog of the Aristotle University of Thessaloniki, during a significant period of 45 years, from 1970 until 2015. From the calculations of b values and earthquake density in certain regions asperity patterns have been observed: asperity located by small b values and low densities coincide with proposition of possible asperity found in literature. Based on these facts we reproduce the hypothesis of an Asperity in the south area of Corinth Gulf between the Helike and Xilokastro faults.